Geotechnical conditions and seismic hazard analysis for architecture heritage preservation in Peru: The Andahuaylillas Church case study - Pando M.A. (2016)
This chapter presents the results of a geotechnical and geophysical tests and a Deterministic Seismic Hazard Assessment (DSHA) carried out for the San Pedro Apostol de Andahuaylillas church in Peru, also known as the Sistine Chapel of the Andes for its magnificent paintings. The DSHA is one of the key components of the ongoing seismic vulnerability study led by the Engineering and Heritage research group of the PUCP University, in Lima, Peru. This structural seismic vulnerability study is motivated primarily because of the historical, architectural and artistic features of this church, built circa the late 16th or early 17th century, which was declared part of the Cultural Heritage of Peru in 2010. The church was built by the Jesuits in the sixteenth century over a pre-colombian huaca. Construction for the church was in two main phases. In 1570 construction started with a small chapel and the nave and main facade were completed in 1606.